Narrow band green light effects on headache, photophobia, sleep, and anxiety among migraine patients: an open-label study conducted online using daily headache diary - Lipton, Richard B.; Melo-Carrillo, Agustin; Severs, Mark; Reed, Michael; Ashina, Sait; Houle, Timothy; Burstein, Rami (Frontiers in Neurology, 2023)
Background: narrow band green light (NbGL) has been shown to relieve headache in small numbers of subjects but large-scale real-world assessments are lacking. The goal of this prospective, observational, open-label, real world study was to determine whether treatment with NbGL during the ictal phase of migraine, improves patients' perception of their headache, photophobia, anxiety and same-night sleep. Methods: The study was conducted in purchasers of the NbGL Lamp in two phases. In Phase I purchasers of the Lamp completed a survey and were asked to participate in a 6-week diary study. In Phase 2 participants completed daily diaries for 6 weeks. Specifically, they were asked to use their judgement/impression/perception when choosing between headache-improved or headacheunimproved after using the NbGL during acute attacks. Diary outcomes of interest included rates of attacks improve in responders (≥50%), non-responders (<50%), super-responders (≥75%) and super non-responders (<30%). Results: Of 3,875 purchasers of the Lamp for migraine, 698 (18%) agreed to participate, filled out a pre-study survey, and agreed to a 6-week daily headache diary. Complete data were provided by 181 (26%) participants. Using criteria above, 61, 39, 42 and 27% of participants were classified responder, non-responder, super-responder and super non-responder, respectively. Headache improved in 55% of all 3232 attacks, in 82% of the 1803 attacks treated by responders, and in 21% of the 1429 attacks treated by non-responders. Photophobia improved in 53% of all attacks, 68% of the attacks in responders and in 35% of the attacks in non-responders. Anxiety improved in 34% of all attacks, 46% of the responders' attacks, and 18% of the non-responders' attacks. Sleep improved in 49% of all attacks, 59% of the responders' attacks, and 36% of the non-responders' attacks.This open-label real world study suggests that 2 hours of treatment with the lamp during migraine attacks is associated with relief of pain and photophobia, reduction in anxiety, and improved sleep. The absence of rigorous diagnosis and a blinded contemporaneous control group limits the rigor of this interpretation. Improvement in photophobia, anxiety and sleep among the responders may be secondary to the improvement in the headache itself.